Intertidal echinoderm identification keys for a reef-walking-tour at Mandalika, Lombok Island, Indonesia - IMAM BACHTIAR; ENI SUYANTRI; TRI AYU LESTARI; MUHAMMAD IRSYAD A. GHAFARI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Bachtiar I, Suyantri E, Lestari TA, Ghafari MIA. 2024. Intertidal echinoderm identification keys for a reef-walking-tour at Mandalika, Lombok Island, Indonesia. Biodiversitas 25: 1965-1974. The coastal biodiversity of Lombok Island has not been utilized holistically for tourist destinations. The Special Economic Zone (SEZ) of Mandalika, Central Lombok District, West Nusa Tenggara Province, Indonesia was established on the island's southern coast, designed to be an ecoresort with thousands of super-premium rooms. New tourist attractions are therefore required to fulfill the increasing demands. The present study aims to provide a pre-requisite science to develop a new tourist attraction related to marine biodiversity in intertidal areas. An intertidal reef walking tour will be initiated to add existing ecotourism options on the island. Culturally, the intertidal area is used for reef gleaning and seaweed farming. The gleaning tradition has the potential to be integrated into the reef walking tour as the cultural menu of ecotourism. The present study offers identification keys for echinoderm fauna inhabiting the intertidal area of the Mandalika SEZ. The identification keys are new and designed specifically for tourist users with broad discipline backgrounds. Twenty-five echinoderm fauna can be identified using the new tourism-designed keys. The echinoderm keys may apply to intertidal areas of many islands in the Indonesian Archipelago and the Western Pacific.